Genome-Wide Screening of Differentially Expressed Genes and their Potential Associations with Aging Dental Pulp Stem Cells - Ma, Xiaocao; Liu, Hongchen; Zheng, Ying; Dai, Yawen; Lingling, E.; Zhang, Rong; Zhang, Shuo (Combinatorial Chemistry & High Throughput Screening, 2023)
Background: Dental pulp stem cells (DPSCs) refer to a type of stem cells, which is characterized by great differentiation potential and is easy to obtain. DPSCs are able to be employed for treating immune diseases and tissue regeneration. However, the differentiation ability exhibited by aging DPSCs is reduced, thereby limiting the application. As speculated by the microarray analysis, different expressions of miRNAs might be involved in DPSC senescence, whereas comprehensive transcriptome level detection has been rare. Objective and Methods: To gain insights into the molecular mechanisms involved, RNA-sequencing, pathway enrichment and Gene Ontology Analysis were conducted on aging and young DPSCs. Results: In this study, the differences in long non-coding RNA (lncRNA) and messenger RNA (mRNA expressions) of the aging and young DPSCs were demonstrated, and the vital factors and the relevant pathways were speculated. On the whole, 18950 mRNAs and 21854 lncRNAs were detected, among which 14 mRNAs and 7 lncRNAs were differentially expressed. Furthermore, hsa-miR-6724-5p may be a vital node in the aging process of DPSCs, and its target genes was involved in the dopaminergic synapse. Conclusion: In brief, the aging of DPSCs was significantly dependent of differentially expressed genes (DEGs) which is related to dopaminergic synapse. However, the specific function and internal relationship of the DEGs should be verified in depth.
Keywords: nervous system